2012
DOI: 10.1103/physreva.85.023617
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature phase diagram of two-component bosons in a cubic optical lattice: Three-dimensionalt-Jmodel of hard-core bosons

Abstract: We study the three-dimensional bosonic t-J model, i.e., the t-J model of "bosonic electrons," at finite temperatures. This model describes the s = 1 2 Heisenberg spin model with the anisotropic exchange coupling J ⊥ = αJ z and doped bosonic holes, which is an effective system of the Bose-Hubbard model with strong repulsions. The bosonic "electron" operator B rσ at the site r with a two-component (pseudo)spin σ (= 1,2) is treated as a hard-core boson operator. By means of Monte Carlo simulations, we study its f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In the present paper, we regard the B-t-J model is a canonical model for the strong on-site repulsive Bose-gas system. Hamiltonian of the B-t-J model is given as follows [8][9][10][11]14 ,…”
Section: Bosonic T-j Model With Ddi and Derivation Of Effective Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, we regard the B-t-J model is a canonical model for the strong on-site repulsive Bose-gas system. Hamiltonian of the B-t-J model is given as follows [8][9][10][11]14 ,…”
Section: Bosonic T-j Model With Ddi and Derivation Of Effective Mmentioning
confidence: 99%
“…The previous numerical study of the B-t-J model 9,10,16 showed that there appear various phases including superfluid (SF) with Bose-Einstein condensation (BEC), state with the pseudo-spin long-range order, etc. For the most of the parameter regions, the QMC show that the density fluctuation of particles at each lattice site is stable even in the spatially inhomogeneous states like a phaseseparated state.…”
Section: Bosonic T-j Model With Ddi and Derivation Of Effective Mmentioning
confidence: 99%
“…Physical Hilbert space of the system consists of states with total particle number at each site less than unity (the local constraint). In order to incorporate the local constraint faithfully, we use the following slave-particle representation 10,11 ,…”
Section: Bosonic T-j Model and Derivation Of Effective Modelmentioning
confidence: 99%
“…The case of J = 0, J z > 0 will be investigated in the subsequent subsection. For the ferromagnetic case J < 0 and |J| > |J z |, it is readily expected that the system has a similar phase diagram to that on the cubic lattice 9) as there are no frustrations in the system. One of the motivations to study the doped AF magnets on the triangular lattice comes from the possible spin liquid and superconductivity suggested by Anderson,20) and therefore we focus on the AF cases.…”
Section: T-j Xy Modelmentioning
confidence: 99%
“…The system H tJ might be derived as an effective model of Bose-Hubbard model that describes a cold atom system in an optical lattice. 8,9) In this case, J and J z are related to the intra-species and inter-species on-site repulsions, and J < 0. In this paper we study the bosonic t-J model (1) with general interests and treat J and J z as free parameters.…”
Section: Model and Path-integral Formalismmentioning
confidence: 99%